Magotaro: An eighteenth century Japanese sailor’s record of insular Southeast Asia - Nomura Toru, (Universiti Kebangsaan Malaysia, 2009)
Although called Magoshichi, the eighteenth century Japanese adventurer, Mogataro, born probably in 1747, was referred to as Magotaro, based on the transcript of his interview at the Nagasaki Magistrate Office. The same name is used in another record, Oyakugashira Kaisen Mokuroku, a business record of the Tsugami family, a shipping agent in Magotaro’s home village. In this paper, I attempt to trace his experiences in a number of documents and records. Some are reliable, while the others not. The most important and accessible source is An Account of a Journey to the South Seas. It contains an account from an interview with him in his old age. Another important official document about him is Ikoku Hyoryu Tsukamatsurisoro Chikuzen no Kuni Karadomari Magotaro Kuchigaki, which is the transcript of the Nagasaki Magistrate Office’s interrogation of Magotaro when he arrived in Nagasaki in 1771. There is also Oranda Fusetsugaki Shusei submitted to Natsume Izumizunokami Nobumasa, the Nagasaki Magistrate, by Arend Willem Feith, the captain of the Dutch ship aboard which Magotaro was repatriated. The other sources, including manuscripts, have a more or less literary flavor but are not reliable